2021
DOI: 10.1111/epi.16815
|View full text |Cite
|
Sign up to set email alerts
|

The ILAE classification of seizures and the epilepsies: Modification for seizures in the neonate. Position paper by the ILAE Task Force on Neonatal Seizures

Abstract: Seizures are the most common neurological emergency in the neonatal period and in contrast to those in infancy and childhood, are often provoked seizures with an acute cause and may be electrographic‐only. Hence, neonatal seizures may not fit easily into classification schemes for seizures and epilepsies primarily developed for older children and adults. A Neonatal Seizures Task Force was established by the International League Against Epilepsy (ILAE) to develop a modification of the 2017 ILAE Classification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
289
1
17

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(310 citation statements)
references
References 98 publications
(195 reference statements)
3
289
1
17
Order By: Relevance
“…Consistent with recent studies, 28–30 we have shown that phenobarbital is generally ineffective in neonatal genetic epilepsies, as it resulted in persistence or early recurrence of seizures in eight of nine infants. The most recent ILAE position papers for classification of epilepsies 18,21 incorporate etiology along each stage of the classification. However, when it comes to neonates, we are a step behind, as the critical and clinically essential distinction between acute provoked seizures and seizures as a manifestation of genetic epilepsies is rarely made in the neonatal ICU 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with recent studies, 28–30 we have shown that phenobarbital is generally ineffective in neonatal genetic epilepsies, as it resulted in persistence or early recurrence of seizures in eight of nine infants. The most recent ILAE position papers for classification of epilepsies 18,21 incorporate etiology along each stage of the classification. However, when it comes to neonates, we are a step behind, as the critical and clinically essential distinction between acute provoked seizures and seizures as a manifestation of genetic epilepsies is rarely made in the neonatal ICU 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings highlight the importance of correct interpretation of seizure semiology in neonates and the use of appropriate descriptive terminology. This emerging approach requires the elimination of the old monolithic notion of “neonatal seizures” as a single entity, and the acknowledgment that seizures in the nursery may be either acute provoked or the manifestation of neonatal epilepsies 21 . Those two conditions are different, and for each there are different etiologies, including rare or ultrarare disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I agree with the task force that although "BRDs are considered to be electrographically distinct from neonatal seizures, in practice they indicate pathology and often co-occur with electrographic seizures." 3 This does not mean that, based upon today's evidence, BRDs should be considered seizures and treated as such. This area of controversy must be addressed as new studies of neonatal seizures are designed, current studies are reported, and existing data are interpreted in the present clinical context.…”
Section: A Major Change To the Definition Of Eeg Seizures Is Proposedmentioning
confidence: 99%
“…Focal seizures include focal aware, focal impaired awareness, focal motor, focal non‐motor, and focal to bilateral tonic‐clonic. Given unique neonatal considerations, a new ILAE Classification for neonatal clinical seizures includes the most prominent feature and delineates between two groups: motor vs nonmotor 5 . Motor seizures include automatisms, clonic, spasms, myoclonic, sequential, and tonic.…”
Section: Clinical Seizuresmentioning
confidence: 99%